Soybean Value Chain: A Climate-Smart Agriculture Approach - An Extension Workers Manual - Ministry of Agriculture, Animal Industry and Fisheries, Uganda (2023)
The manual is designed to assist the reader with information about soybean value chain and its management in times of climate change. It is comprised of six chapters of coordinated content as summarized below. First chapter of this manual is focused on the soybean and its development and also describes the status of soybean in Uganda and its significance. Chapter two introduces the concept of climate change and the three pillars of climate smart agriculture which are important for decision making in implementation of Climate Smart Agriculture (CSA) practices and focuses on the major constraints to soybean production which are attributed to weather and climatic variations and how they impact productivity. Chapter three presents the climate resilient field management processes which begin with selection of the appropriate soybean variety to planting and pests which include insects, aphids, bugs, worms, and others; and diseases such as fusarium root rot and their management a0nd control methods including integrated pest management prioritizing biological control and organic substances. The safe use of agrochemicals is recommended as a last option. Chapter four describes the best post-harvest management practices and technologies with some illustrations for emphasis. Chapter five introduces the component of record keeping and calculation of profits and losses and shows potential for generating a gross income per acre. The manual integrates a gender component and maps out its interaction with CSA to support users in appreciation of gender responsiveness in implementation of CSA interventions and planning for capacity enhancement. For instance, early postharvest handling is done by women and as such, tools, knowledge, and skills for the same would ensure women are largely involved. It is critical for the users of the manuals to appreciate the dynamism of this information and make provision for adjustments based on the setting and the times. The manual concludes by presenting an array of environmental restoration practices which are key in climate smart agriculture.